THERMAL INSULATION BOARDS FROM COCONUT PITH - RAO, C V. N.; PRABHU, P V; VENKATARAMAN, R (Fishery Technology, 2025)
Processing technique and physical characteristics of thermalinsulation boards prepared from coconut pith using rubber latexas the binding agent are reported in this communication. In viewof the easy processing, low cost and comparable physical propertieswith other insulating materials availble indigenously, manufactureof these boards appears to be promising,